THE TREND OF DAGESTAN’S YOUNG MOSLEM GENERATION TOWARDS DIGITAL PLATFORMS AND THE RESPONSIBILITY OF LOCAL ULAMA THROUGH SOCIAL MEDIA - Mumtazah, Yasmin; Fahrurodji, Ahmad (International Review of Humanities Studies, 2023)
This study discussed the tendency of the young moslem generation of Dagestan in using social media such as YouTube, Instagram, and VKontakte. The goal of this research was to answer the responsibility of related ulama on the digital platform used by Dagestan's young generation. The netnographic method was employed as a tool to assist researchers in communicating via digital platforms. According to the findings of the netnographic research, social media is not a solution to the problems of Dagestan Muslims. Although social media was a gathering place for the younger generation to learn about Islam, this did not guarantee that all activities carried out by Muftiyat RD through digital platforms would be approved by users. Therefore, social media was only a tool to facilitate the spread, not to solve the problems of the people.